2011
DOI: 10.3748/wjg.v17.i37.4235
|View full text |Cite
|
Sign up to set email alerts
|

Three initial diets for management of mild acute pancreatitis: A meta-analysis

Abstract: The non-liquid soft or solid diet did not increase pain recurrence after re-feeding, compared with the clear-liquid diet. The non-liquid diet reduced hospitalization.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
16
0
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(18 citation statements)
references
References 27 publications
1
16
0
1
Order By: Relevance
“…Moreover, the use of this diet for long‐term nutrition is significantly hampered, as patients can become deficient in other nutrients such as essential fatty acids. Although a liquid diet has previously been advocated in the setting of a flare of acute pancreatitis, a meta‐analysis showed no difference in pain score compared with a solid diet, with the negative addition of fewer calories consumed …”
Section: Management Of Nutritionmentioning
confidence: 98%
“…Moreover, the use of this diet for long‐term nutrition is significantly hampered, as patients can become deficient in other nutrients such as essential fatty acids. Although a liquid diet has previously been advocated in the setting of a flare of acute pancreatitis, a meta‐analysis showed no difference in pain score compared with a solid diet, with the negative addition of fewer calories consumed …”
Section: Management Of Nutritionmentioning
confidence: 98%
“…20 These studies have only detected a shorter duration of hospital stay among patients treated with complete or immediate refeeding. 16,17,19,20 Accordingly, we decided to analyze the frequency of intolerance to refeeding in mild AP, treatment performed, and the variables related to intolerance in a consecutive series of patients.…”
mentioning
confidence: 99%
“…A meta-analysis of three RCTs with 326 patients with mild acute pancreatitis showed that a solid diet reduced the length of hospital stay, compared to a liquid diet, but did not affect the rates of recurrent pain after refeeding [90]. Decreased length of hospital stay has also been shown in the most recent RCTs with a solid as opposed to a liquid diet in mild acute pancreatitis [91,92].…”
Section: Nutritionmentioning
confidence: 90%